Infant oral health care: a review on parent’s role in infant oral health - Singh, Raghavendr; Lakhanam, Medha (International Journal Of Community Medicine And Public Health, 2021)
The maintenance and prevention of oral health is one of major concern of parents. Dental caries is one of most common oral manifestation because of lack of knowledge and improper techniques. The first visit should be planned at early ages only so that proper guidance and knowledge should be imparted to the parent to prevent oral diseases. The first visit should include oral screening, oral habit monitoring, Brushing technique demonstration and fluoride application if needed. There should be more involvement to strengthen the role of pediatricians’ in children’s oral health requires an understanding of their current knowledge and practice. In this scoping review, we aimed to comprehensively map what is known about the knowledge and practice of parents regarding children’s oral health.